2009
DOI: 10.1097/jto.0b013e31819d18e5
|View full text |Cite
|
Sign up to set email alerts
|

A Structured Exercise Program for Patients with Advanced Non-small Cell Lung Cancer

Abstract: Introduction Exercise improves functional outcome and symptoms for certain cancer populations, but the feasibility, efficacy, and safety of structured exercise in patients with lung cancer is unknown. In this study, we examined the feasibility of a hospital-based exercise program for patients with advanced non-small cell lung cancer. Methods This study included patients with newly diagnosed advanced stage non-small cell lung cancer and Eastern Cooperative Oncology Group performance status 0–1. A physical the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
161
3
12

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(190 citation statements)
references
References 78 publications
(45 reference statements)
12
161
3
12
Order By: Relevance
“…In this study, patients with advanced incurable cancer were randomized to eight weeks of CAE performed twice weekly in a supervised hospital setting, or to usual care. The increased grip strength in the CAE relative to UC supports previous uncontrolled trials in advanced cancer [47,48] on efficacy of exercise on muscle strength also in this population. In conclusion, the findings from our review support the effect of exercise on muscle strength in cancer patient undergoing curative treatment.…”
Section: Populationssupporting
confidence: 83%
See 1 more Smart Citation
“…In this study, patients with advanced incurable cancer were randomized to eight weeks of CAE performed twice weekly in a supervised hospital setting, or to usual care. The increased grip strength in the CAE relative to UC supports previous uncontrolled trials in advanced cancer [47,48] on efficacy of exercise on muscle strength also in this population. In conclusion, the findings from our review support the effect of exercise on muscle strength in cancer patient undergoing curative treatment.…”
Section: Populationssupporting
confidence: 83%
“…As only RCT's were included, two uncontrolled trials performed in patients with advanced lung cancer [47,48] were not described in our results. These trials showed improvement in muscle strength after eight weeks of CAE but none of these studies used muscle mass as outcome.…”
Section: Study Limitationsmentioning
confidence: 99%
“…However, studies have suggested that there is value in those with lung cancer maintaining a certain level of physical activity. Pertinently, cancer symptoms have been shown to significantly decrease in inoperable lung cancer patients after just eight weeks of physical activity, which also prevented a decrease in cardiovascular fitness (Temel et al, 2009). …”
Section: Recurrence and Mortalitymentioning
confidence: 99%
“…In light of these considerations, it's clear that there is a growing interest in the identification of strategies to enable patients suffering from NSCLC to improve exercise tolerance, anxiety and depression, which are the main factors involved in the decline in their quality of life; in this scenario, PR with specific muscular exercises may play a decisive role [25][26][27]. This review is intended to analyze the most recent literature: in recent years, in fact, many articles have reported on the potential role of PR in the management of patients with not-operable NSCLC; although the evidence regarding its efficacy on symptoms has not been proven yet, the general impression that emerges is that respiratory exercises represent a valid and useful strategy to adopt in the overall management of these patients.…”
Section: Introductionmentioning
confidence: 99%